Siwak as a prophetic and evidence-based oral hygiene tool: a qualitative study among Islamic scholars - Haslinda Ramli,; Shahida Mohd Said,; Ahmad Munawar Ismail,; Tuti Ningseh Mohd Dom, (Penerbit Universiti Kebangsaan Malaysia, 2023)
Oral hygiene care and practice, siwak, which adopts Prophet Muhammad’s (Peace be upon Him, hereafter, PBUH) sunnah, remains unclear. As such, this study aims to explore and critically appraise the Prophetic practice of siwak according to Islamic literature, and in the light of current clinical evidence to clarify siwak as the oral hygiene practice prescribed by the Prophet (PBUH). Semi-structured one-to-one interviews was conducted among local contemporary Islamic scholars. The questions prepared were based on literature review and focused on toothcleaning practices of the Prophet (PBUH) as well as how the siwak was prepared and kept, as reported in documented narrations. Interview transcripts were analysed using thematic approach while content analysis of the referred narrations of hadith was made to provide a triangulation of the overall siwak use framework. The investigation revealed that horizontal tooth-brushing was highly recommended, and that al-Arak tree sticks are preferred to be 1) specifically prepared, 2) held steadily in the right hand, 3) used between two to five minutes depending on the goal, and 4) hygienically stored. It was also found that improper siwak practice may significantly suppress the clinical advantages. Thus, these findings substantiate future evidence-based guidelines on optimal oral hygiene care for siwak user based on authentic Islamic source.